Harvesting energy via stimuli‐free water/moisture dissociation by mesoporous SnO2–based hydroelectric cell and CuO as a pump for atmospheric moisture. (25th November 2019) - Solanki, Vanaraj; Krupanidhi, Saluru Baba; Nanda, Karuna Kar
Summary: Water dissociation, in general, requires external stimuli such as light energy or electricity. Here, we present a stimuli‐free water dissociation using mesoporous SnO2 –based hydroelectric cell that can directly be exploited to generate electric power for portable applications. The device configuration is almost identical to metal‐air batteries but follows altogether a different reaction pathway. The mesoporous SnO2 –based hydroelectric cell dissociates water molecule into hydroxyl ions (OH ‐ ) and hydronium ion without any stimuli, transports hydronium ions to the opposite end, and simultaneously acts as the separator. The OH ‐ react with Al electrode to release the electrons, whereas hydronium ions get reduced at the Ag electrode to produce a potential difference as high as ~1000 ± 20 mV between the electrodes that is stable over 3500 hours. The device also shows its potential toward electric power generation from atmospheric moisture with the help of CuO layer that acts as moisture pump. Abstract :